Civilization crisis and urban crisis - Calderón Cockburn, Julio (2019)
The article addresses the relationship between the civilizational crisis and urban crises that cities have experienced in recent decades. In the West, it went from the urban crisis, located in the social economic system and political legitimacy, to the “disappearance of cities”, in which the community has ceased to be founded in the proximity or local population density. In Latin America, the urban crisis of the twentieth century in Europe and the United States is rather the normal situation of its cities, and the civilizational crisis has worsened this situation, characterized by informality and the lack of adequate housing.